Sustainable Dreams and Unsustainable Development: Dishonest Discourses on Kenyan Education Researches - Osabwa, Wycliffe (African Journal of Education,Science and Technology (AJEST), 2018)
The term ‘development’ has many referents. Often times, it has been employed in a sense that captures the traditional trichotomy: social, political and economic. Whereas a great number of individuals regard development in terms of physical structures, the truth is that the axis of real development lies in human resource. From here flows ideas; ideas that are crystalized to give rise to all other forms of development. It is an understatement to assert that human resource development is the most progressive, the most sustainable form of development. And this is founded upon education. Such education must be qualified based on its proclivity to address current needs; its employment of appropriate means of transmission; and its accessibility to those who require it. Above all, it must be one that can be sustained so that it equally guarantees sustainability of its outcomes. This paper addresses not how research and innovation in education can lead to sustainable development, but rather, why the prevailing researches in education – specifically in Kenya – have failed to produce innovations, leave alone sustainable development. One can only sustain that which is present in the first place. The paper will make reference to some Kenyan educational research practices and orientations, and employ the philosophical reflection method to critically provide an insight into the vanity that passes for education research. This will in essence explain why innovation and development have remained a mirage such that citizens now cast doubts on the necessity of education. The paper will be a candid discourse that sums up the thesis statement: deficient educational researches lead to deficient education systems which in turn produce deficient human resource that can never realize any meaningful development.